ANALISIS KONTRASTIF KALIMAT PASIF DALAM BAHASA INDONESIA DAN BAHASA ARAB - Muhamad Hilal Adriyansyah; Siti Elza Al Humaeroh; Saniaturrohmah (Hijai - Journal on Arabic Language and Literature, 2025)
This study aims to analyze the comparison between passive sentences in Indonesian and Arabic using a contrastive linguistic approach. Passive sentences in these two languages show significant differences in structure and usage, although both serve to emphasize the object of an action. The method used includes a descriptive analysis of a corpus of passive sentences from Indonesian and Arabic sources. The results of the study indicate that passive sentences in Indonesian tend to be more flexible in terms of structure, while Arabic has stricter rules regarding verb and subject changes. The implications of these findings are important for language teaching and translation, as well as for further comparative linguistic studies. Keywords: passive voice, contrastive linguistics, syntax